Dorsoventral axis formation in the Drosophila embryo - Shaping and transducing a morphogen gradient. - Moussian, B.; Roth, S. (Current Biology, 2005)
The graded nuclear location of the transcription factor Dorsal along the dorsoventral axis of the early Drosophila embryo provides positional information for the determination of different cell fates. Nuclear uptake of Dorsal depends on a complex signalling pathway comprising two parts: an extracellular proteolytic cascade transmits the dorsoventral polarity of the egg chamber to the early embryo and generates a gradient of active Spätzle protein, the ligand of the receptor Toll; an intracellular cascade downstream of Toll relays this graded signal to embryonic nuclei. The slope of the Dorsal gradient is not determined by diffusion of extracellular or intracellular components from a local source, but results from self-organised patterning, in which positive and negative feedback is essential to create and maintain the ratio of key factors at different levels, thereby establishing and stabilising the graded spatial information for Dorsal nuclear uptake.